Peningkatan Loyalitas Melalui Kepercayaan - Selly Viani; Meutia Meutia; Hayati Nupus (Magister Manajemen - Universitas Sultan Ageng Tirtaysa, 2022)
This study observes impact of E-EOM to increase the loyalty of BPJS participant that registered in Ikhlas Medika 2 clinic through trust as mediating variable. Study was conducted in Ikhlas Medika 2 clinic, using quantitative method by collecting primary data by filling out questionnaire. Population in this study was BPJS participants registered in Iklhas Medika 2 clinic that made sick visits during August 2019 - December 2020, which was 1537 people. Sample size for this study is 170 samples. SmartPLS 3.29 program was used as tool for analysis. As a result, we found that trust was able to mediate E-WOM and Service Quality to participants' loyalty. This study found that E-WOM has positive impact but not significant to BPJS participants loyalty in Ikhlas Medika 2 Clinic, shown by coefficient interval original 0.08 and T statistic 1.142, and p value 0.254.Keywords : E-WOM, Service Quality, Loyalties, Trust